Understanding human resource management practices in Botswana's public health sector. Issue 8 (21st November 2016) - Seitio-Kgokgwe, Onalenna Stannie; Gauld, Robin; Hill, Philip C.; Barnett, Pauline
Abstract : Purpose: The purpose of this paper is to assess the management of the public sector health workforce in Botswana. Using institutional frameworks it aims to document and analyse human resource management (HRM) practices, and make recommendations to improve employee and health system outcomes. Design/methodology/approach: The paper draws from a large study that used a mixed methods approach to assess performance of Botswana's Ministry of Health (MOH). It uses data collected through document analysis and in-depth interviews of 54 key informants comprising policy makers, senior staff of the MOH and its stakeholder organizations. Findings: Public health sector HRM in Botswana has experienced inadequate planning, poor deployment and underutilization of staff. Lack of comprehensive retention strategies and poor working conditions contributed to the failure to attract and retain skilled personnel. Relationships with both formal and informal environments affected HRM performance. Research limitations/implications: While document review was a major source of data for this paper, the weaknesses in the human resource information system limited availability of data. Practical implications: This paper presents an argument for the need for consideration of formal and informal environments in developing effective HRM strategies. Originality/value: This research provides a rare system-wide approach to health HRM in a Sub-Saharan African country. It contributes to the literature and evidence needed to guide HRM policy decisions and practices